Ethics in international arbitration - Rogers, Catherine A. (Oxford (UK) Oxford University Press, 2014)
Although international arbitration is a remarkably resilient institution, many unresolved and largely unacknowledged ethical quandaries lurk below the surface. This text provides a framework for developing much-needed formal ethical rules and a reliable enforcement regime in the international arbitration system--
I. Mapping the terrain -- From an invisible college to an ethical No-Man's Land -- Arbitrators, barbers, and taxidermists -- Attorneys, barbarians, and guerrillas -- Experts, partisans, and hired guns -- Gamblers, loan sharks, and third-party funders -- II. Staking out theoretical boundaries and building the regime -- Chanticleer, the fox and self-regulation -- Ariadne's thread and the functional thesis -- Herodotian myths and the impartiality of arbitrators -- Duck-rabbits, a panel of monkeys, and the status of international arbitrators -- Castles in the air and the future of ethics in international arbitration.
Includes bibliographical references and index.
Keywords: International commercial arbitration -- Moral and ethical aspects; Arbitrators -- Legal status, laws, etc; Legal ethics; Arbitrators -- Legal status, laws, etc; Legal ethics; Law; jogi etika; x